Design and build a hotel service reservation and verification system using web-based e-KTP - Hadi, Achmad Farchan; Taufik, Mochammad; Hudiono, Hudiono (Politeknik Negeri Malang, 2023)
Hotel is a company that provides accommodation services and provides other facilities that meet the requirements of comfort and commercial purposes. The development of the times and technology, also affects the development of the hotel. The use of hotel reservation technology makes it easier for the hotel booking process. Service quality, trustworthiness, facilities and security affect hotel selection decisions. A common application of security technology is the use of duplicable RFID card lock technology. For this reason, it is necessary to add a double security system in the form of an OTP (One Time Password) code and limit access to visitors and visitors from visitors. The test results using NFC PN532 to read e-KTP cards obtained readings in under 1.00 seconds, with 100% accuracy within a distance of 0 - 2.5 cm. In testing with an additional OTP (One Time Password) code, the results obtained are good accuracy readings with an accuracy rate of 100% when the OTP code is appropriate.